Conflict between the Thai and Islamic cultures in Southern Thailand (Patani) 1948-2005 - Walker, Dennis P. (Penerbit Universiti Kebangsaan Malaysia, 2005)
This study reviews cultural factors in the development of secessionist Muslim nationalism in the area of Southern Thailand historically termed Patani, consisting of the current provinces of Narathiwat, Pattani, Yala and the linguistically more Thaiized Satun (Setul). The culture and language of most of the South has continued to have more affinities to Muslim areas of northern Malaysia than with Buddhist-majority Thailand, in the face of repeated drives by Thai administrations to Thaiize these Muslim populations since 1902. The study reviews the development of the State.s monolingual Thai-medium schools as the main tool with which successive Thai governments tried to integrate the South.s Muslims into a united Thai state. Such deculturization stimulated armed insurgency by some Muslim Malays in Thailand from the later 1960s. The essay traces how various more liberal Thai administrations since 1990 at least made efforts to educate its Muslims and bring development and jobs with a view to drain away the economic grievances that could feed further insurgency. However, the creation of an unprecedented class of Thai-literate Muslim politicians within parliamentarism could not make the Thai civil servants responsive enough to the grievances of either the Muslim poor or of the marginalized Islamic educationalist counter-elite. In 2004 inter-communal violence and insurgency duly exploded across the Muslim South